1992
DOI: 10.1128/mcb.12.11.4872
|View full text |Cite
|
Sign up to set email alerts
|

Identification of binding sites on the regulatory A subunit of protein phosphatase 2A for the catalytic C subunit and for tumor antigens of simian virus 40 and polyomavirus.

Abstract: Protein phosphatase 2A is composed of three subunits: the catalytic subunit C and two regulatory subunits, A and B. The A subunit consists of 15 nonidentical repeats and has a rodlike shape. It is associated with the B and C subunits as well as with the simian virus 40 small T, polyomavirus small T, and polyomavirus medium T tumor antigens. We determined the binding sites on subunit A for subunit C and tumor antigens by site-directed mutagenesis of A. Twenty-four N-and C-terminal truncations and internal delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
162
0
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(181 citation statements)
references
References 79 publications
17
162
0
2
Order By: Relevance
“…22 Importantly, we have shown that in every case the mutation renders the A␣ subunit defective in binding B or C subunits, depending on whether the mutation is located in the N-terminal B subunit binding domain (repeats 1-10) or in the C-terminal C subunit binding region (repeats [11][12][13][14][15] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Importantly, we have shown that in every case the mutation renders the A␣ subunit defective in binding B or C subunits, depending on whether the mutation is located in the N-terminal B subunit binding domain (repeats 1-10) or in the C-terminal C subunit binding region (repeats [11][12][13][14][15] (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…B subunits bind to repeats 1-10 and the C subunit to repeats 11-15. 15,16 B and C subunits physically interact while bound to A␣ (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-treated and excysting cysts (in Stages 1 and 2 and 30 and 60 min excystation) were dried on the coverslips. Subsequently, cytoskeletons, permeabilized trophozoites and cysts were blocked for 1 h in blocking buffer (5% goat serum, 1% glycerol, 0.1% bovine serum albumin, 0.1% fish gelatin and 0.04% sodium azide) and incubated for 1 h with the (nonmethylation sensitive) rabbit anti-PP2A-C polyclonal antibody directed against a synthetic peptide (KVTRRTPDYFL) corresponding to the C terminus of the human PP2A-C subunit [25] or the mouse monoclonal antibody against CWP-1 [26]. As a control for specificity, the Giardia C-terminal PP2A-C peptide 'HISRRVPDYFL' (GenScript Corporation) was preincubated for 30 min with the PP2A-C antibody.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…For detection with the methylation sensitive antibody, filters were treated for 10 min with 0.2 M KOH prior to blocking of the membrane; control membranes were untreated. Filters were incubated with either the methylation sensitive (Ab 299/309 ) [29] or the non-methylation sensitive anti-PP2A-C polyclonal antibody [25], the rabbit polyclonal antibody against PDI-2 [30] as a protein loading control or the mouse monoclonal antibody against CWP-1. As a control for specificity, the KVTRRTPDYFL peptide used for immunization [25] or the Giardia C-terminal PP2A-C peptide HISRRVPDYFL (GenScript Corporation) was pre-incubated with the non-methylation sensitive PP2A-C antibody for 30 min.…”
Section: Western Blot Analysismentioning
confidence: 99%